An Analytical study of Fine Needle Aspiration Cytology in Various Thyroid Lesions and their Correlation with Histopathology - Sharma, Anjana; Singh, Avishesh; Sahu, Ajay (International Journal of Health and Clinical Research, 2021)
Introduction :The efficacy and diagnostic accuracy of FNAC is quite reliable in the hands of well experienced cytopathologist and correlates well with histological diagnosis.The present study was undertaken with the aim of classifying the cytomorphology of palpable thyroid lesions by FNAC and correlate the results with histo- pathology wherever possible.Methods:This Retrospective & Analytical studyinvolved 200 Subjects The period of study was 6 months & all the Information about the patient’s age, sex, ultrasonography findings, and cytological report was recorded.Results: Analysis of various thyroid lesions in relation to age and gender was done, cytohistological correlation was done in all cases, and diagnostic accuracy of FNAC was calculated.Data was filled in Microsoft Excel&analysed using a computer software Epi Info version 6.2 (Atlanta, Georgia, USA)& SPSS .Benign lesions comprised the maximum number of cases 83 % , followed by AUS in 4 % cases. The patients mean age in the malignancy and the suspicious for malignancy category was higher.The sensitivity for cytological diagnosis of neoplasia was 95.7%, specificity 100% and diagnostic accuracy of 96.0%, showing a good positive correlation with histopathology. Results were comparable with the previous published data.Conclusion: FNAC is an invaluable tool in the management of thyroid lesions with a high degree of accuracy. It is safe, simple, cost-effective procedure with absence of major complications and can be performed on out- patients with wide patient compliance. FNAC provides a more rapid and accurate diagnosis of thyroid lesions than any other combination of clinical laboratory tests. Keywords: FNAC , TBSRTC , Thyroid Nodule , Bethesda Classification.